Fear-based health messages for Malay diabetes patients in Singapore - Kawaja, Ariffin (Nanyang Technological University, 2021)
Diabetes is a major cause of death worldwide and ranks amongst killer diseases such as cancer and cardiovascular diseases. The Malays with Type 2 diabetes were being investigated in this research as they are the most susceptible to the disease compared to the other ethnic groups in Singapore. Among the non-clinical intervention programmes, scholarly articles suggest that emotion-based health messages can be a powerful driver to promote health preservation attitudes and behaviours. The objective of this research was to investigate the influence of fear-based messages on patients' behaviours in managing their diabetes condition. To achieve this objective, the research was divided into three phases.